OER Mainstreaming in Tonga - Ishan Sudeera Abeywardena (Athabasca University Press, 2019)
In the race towards achieving the Education 2030 agenda, open educational resources (OER) act as a key enabler for sustainable development goal 4 (SDG4). Leading to the 2014 Regional Focal Points Meeting, Commonwealth of Learning’s (COL) Focal Point for Tonga had identified top priorities for the country where COL can further support the national agenda till 2021. Based on these needs, the Strategic OER Implementation Project in Tonga was initiated by COL in response to a request by the Ministry of Education and Training (MET) of Tonga. The project aims to assist MET in (a) developing a framework for fully utilizing the new fiber optic network infrastructure to deliver online learning to Tongans distributed in the  45 islands; and (b) improve the chances of sustainable livelihoods for Tongan youth by training them in life skills tailored to higher education and employment opportunities in Australia and New Zealand. This paper details the use of the horizontal framework for OER mainstreaming and the OER mainstreaming checklist within this project. The novelty of this project is its approach to mainstreaming OER at an institution in a systemic manner. The contribution this paper makes is to provide a proven plan for sustainable OER mainstreaming in a development setting.